BUSINESS FOR PEACE: PENDEKATAN BARU PBB MELALUI UN GLOBAL COMPACT DALAM PEMBANGUNAN DAN PERDAMAIAN (BUSINESS FOR PEACE : THE NEW APPROACH OF UNITED NATIONS THROUGH UNGC IN DEVELOPMENT AND PEACE) - Yolanda Dwi Adea (MIHI UMY, 2016)
ABSTRACT This study aims to find out why the United Nations, through the UN Global Compact seeks to implement the Business for Peace in various countries, including in the developing world, why this initiative is so important for the business sector, community, and government, as well as how the strategy and implementation in developing countries. By using the concept of social reality, social construction, and positive liberal peace theory in analyzing problems in this study, the results showed that the Business for Peace is important in changing the view and can construct the relationship between the business sector, community, and government. In addition, this platform can mobilize and directing actors from the business sector to be active and effectively plays a role in establishing peace, stability and sustainable development. With common interests and goals, either globally, such as the Sustainable Development Goals (SDGs) as well as other interests, both regionally and nationally, all stakeholders can work together and collaborate to find solutions and actions that appropriate and effective through the UNGC and various platforms, including the Business for Peace.